How do you determine dy/dx given y=x^2+xyy=x2+xy?

2 Answers
Oct 21, 2016

Given a choice, I would solve for yy first.

Explanation:

y=x^2+xyy=x2+xy

Making the function explicit
y-xy=x^2yxy=x2

y = x^2/(1-x)y=x21x

dy/dx = (2x(1-x^2)-x^2(-1))/(1-x)^2dydx=2x(1x2)x2(1)(1x)2

= (2x-x^2)/(1-x)^2=2xx2(1x)2

Leaving the function implicit

y=x^2+xyy=x2+xy

d/dx(y)=d/dx(x^2+xy)ddx(y)=ddx(x2+xy)

dy/dx = 2x +y + x dy/dxdydx=2x+y+xdydx

dy/dx = (2x+y)/(1-x)dydx=2x+y1x

Oct 21, 2016

dy/dx=(2x+y)/(1-x)dydx=2x+y1x

Explanation:

You have to use Implicit Differentiation, which is a special case of the chain rule, and the product rule.

dy/dx=2x+x(1)dy/dx+y(1)dydx=2x+x(1)dydx+y(1)

Simplify

dy/dx=2x+xdy/dx+ydydx=2x+xdydx+y

Solve for dy/dxdydx

dy/dx-xdy/dx=2x+ydydxxdydx=2x+y

Factor out dy/dxdydx

dy/dx(1-x)=2x+ydydx(1x)=2x+y

Isolate dy/dxdydx

(dy/dxcancel(1-x))/(cancel(1-x))=(2x+y)/(1-x)dydx1x1x=2x+y1x

Simplify

dy/dx=(2x+y)/(1-x)dydx=2x+y1x

Here is an example of using the implicit differentiation.